Characterization of dust and crystalline silica exposure during indoor demolition. - Halvorsen, Johanne Ø; Graff, Pål; Gjengedal, Elin Lovise Folven; Ervik, Torunn K (Annals of Work Exposures & Health, 2025)
Exposure to dust and respirable crystalline silica (RCS) is a continuing concern in the construction industry when working with silica-containing materials, such as concrete, brick, or stone. Increased knowledge of the dust characteristics can be used to improve measures to reduce potential exposure. This study aimed to characterize dust collected from indoor demolition in terms of particle size distribution and mineral content, including quartz. Airborne dust was collected with Sioutas cascade impactors at five different construction sites involved in indoor demolition and renovation. Four of the locations had workers demolishing concrete, while at the fifth location brick structures were demolished. An aerodynamic particle sizer (APS) was used to continually monitor the particle number concentrations in the size range 0.54 µm to 17 µm. Material samples of demolished material were collected from each location to determine mineral content. The filters from the Sioutas cascade impactors were weighted to determine dust concentrations in five size fractions ranging from 10 µm down to less than 0.25 µm. Quartz concentrations were quantified with X-ray diffraction using the NIOSH 7500 method and Rietveld refinement was further used to determine other mineral content in the Sioutas impactor samples and material samples. Respirable dust and quartz concentrations were calculated from the Sioutas data. The mass- and number-based particle size distributions measured by the APS were similar for the four locations involved in concrete demolition, whereas the location working with brick had a different distribution. The concentration levels varied widely, and the highest levels were observed at an enclosed location with no natural ventilation where concrete demolition took place. Limited natural or mechanical ventilation led to an accumulation of smaller particles around 1 µm and a lower mass median aerodynamic diameter for RCS, down to 1.2 µm, compared to locations with ventilation. The quartz percentages of the dust collected by Sioutas impactors were found to increase with increasing particle size. The dust contained less quartz than the source material, and an up-concentration of softer minerals like calcite was observed. The knowledge of particle size distributions and concentration levels occurring in the field during indoor demolition is important to ensure effective measures to reduce worker exposure. The results highlight the importance of effective ventilation to reduce the accumulation of airborne particles.